Assessment of Carbon Sequestration Potentials and environmental dynamics in the coastal area of Lagos - T.B. Adedoja; S.A. Adegboyega; A.M. Fakpor (European Scientific Journal, ESJ, 2024)
Coastal environments comprise of multiple arrays of ecosystems, including forests, mangroves, wetlands, and oceans, which play a vital role in long-term carbon storage and mitigation of climate change. These ecosystems possess a unique ability to store carbon for prolonged periods, acting as natural carbon sinks and contributing to the reduction of atmospheric greenhouse gas up concentrations, which is one of the exceptional services they offer. However, despite their significance, the potentials of coastal land covers and their associated land use in mitigating global warming through carbon absorption is often overlooked in current researches. This study employed the InVEST (Integrated Valuation of Ecosystem Services and Trade-offs) model together with Intergovernmental Panel on Climate Change (IPCC) Carbon pool data to assess the carbon stock and dynamics of various land use and land cover types in the coastal environment of Lagos for a period of 20 years. The results revealed a substantial reduction in net stored carbon from 1.33 x 108 metric tons Carbon in 2003 to 1.21 x 108 metric tons of Carbon in 2013, which accounts for a 6.66% decline in stored carbon during that period. Furthermore, the total carbon stock decreased by approximately 3.5 x108 Metric tons, or 2.94%, equating to a loss of over 300 million tons of carbon between 2013 and 2023. Through the identification and measurement of the carbon sequestration capacity of these varied coastal land covers, researchers can gain insight regarding their function in reducing global warming. The preservation and enhancement of these natural carbon sinks can be achieved by conservation efforts, sustainable management practices, and policy decisions informed by this information, thereby aiding in the global fight against climate change.